Counselling users of hearing technology: a comprehensive literature review. (2nd December 2017) - Meibos, Alex; Muñoz, Karen; Schultz, Jared; Price, Tanner; Whicker, John J.; Caballero, Ana; Graham, Laurel
Abstract: Objective : The purpose of this review is to determine the scope of peer-reviewed empirical research related to counselling in audiology with patients using hearing technology and to identify limitations and gaps to guide recommendations for future research. Design : A rapid evidence assessment was used to identify relevant articles for the review. Study sample : Eighteen articles met the inclusion criteria. Results : Three themes were identified: (1) audiologist counselling perspectives, (2) counselling communication trends in practice and (3) audiologist experiences with professional training and reported patient outcomes. Findings revealed audiologists are more confident providing information than counselling that addresses adjustment aspects, and other communication gaps have been observed. Conclusions : There is limited research related to counselling in audiology. Audiologists continue to report a need for more training in counselling in their graduate programmes. Additional research is needed to determine effective ways to implement counselling in practice and to improve graduate student supervision for the development of counselling competencies and confidence in using skills in practice.